Política pública de educação a distância no ensino superior do Brasil: uma avaliação do processo de implementação a partir da experiência da UFMA no Estado do Maranhão - BASTOS, Josie do Amaral (2018)
An evaluation of the implementation process of the Public Policy of Distance Education (EAD) in higher education in Brazil, through the Open University of Brazil (UAB) system, taking as an empirical reference, the experience of the Federal University of Maranhão (UFMA), and municipalities of São Luís and Humberto de Campos in the state os Maranhão. The dialectical critical method is adopted to comprehend the Distance Education program as a phenomenon inserted in capitalist society. It analyzes the emergence and development of the Distance Edu-cation Programa in higher education system and its relation to the current stage of development of capitalism neoliberal ideology, with emphasis on its concrete expressions in the region of Latin America and, particularly in the Brazil. It discusses the dominant education project, aligned with the social and economic demands imposed by neoliberalism and mediated by new technologies, materialized at the local level, more specifically, at the Distance Education Center of the Federal University of Maranhão. The conception and institutional development of Dis-tance Education public policy in Brazil is analyzed in the context of State reform, in line with the guidelines and recommendations of the international agencies, such as the World Bank. The process of implementation of Distance Education (EAD), through the UAB, is evaluated based on the concrete experience developed by the Federal University of Maranhão (UFMA), in the physical support centers (poles) of São Luís and Humberto de Campos. It is concluded that there is a discourse based on the criteria of efficiency that accompanies the public policy of the EAD in the country, expressing itself, at local level, in the poles of São Luís and Humberto de Campos, that is very distant from the public policy guidelines. In addition, the EAD in Brazil, more broadly, responds to the determinations of the globalized capital and the international financing agencies, in favor of national expansion, without a greater commitment to the quality of the education offered.